Making pre-school children wear masks is bad public health - Robert C. Hughes; Sunil S. Bhopal; Mark Tomlinson (Elsevier, 2021)
Children are not small adults. This is a critical point that many pediatricians and other child health professionals get bored of saying, yet it does seem to need repeating. While children have the lowest risk from COVID-19 directly, they risk suffering the indirect impacts of policy decisions, many of which appear to have been made with next to no explicit consideration of their interests. Public health interventions should not only be about infectious disease control, they should consider a broad set of outcomes. In addition, they ought to consider vulnerability, including that in early childhood - a time when young children's brains are developing rapidly and are most susceptible to adversity. We believe that mandating masking of pre-school children is not in line with public health principles, and needs to be urgently re-considered.